ANMCO POSITION PAPER: Network Organization for the Treatment of Acute Coronary Syndrome Patients during the Emergency COVID-19 Pandemic. (27th August 2020) - Scotto di Uccio, Fortunato; Valente, Serafina; Colivicchi, Furio; Murrone, Adriano; Caldarola, Pasquale; Di Lenarda, Andrea; Roncon, Loris; Amodeo, Enzo; Aspromonte, Nadia; Cipriani, Manlio Gianni; Domenicucci, Stefano; Francese, Giuseppina Maura; et al.
Abstract: The COVID-19 pandemic has become a global health emergency. In Italy, the number of people infected by SARS-COVID-2 is rapidly increasing and what emerges from the current data is that the majority do not present any symptoms or only minor flu-like symptoms. In about 20% of the patients, the disease progresses towards more complex forms (interstitial pneumonia to acute respiratory distress and multiple organ failure) with the need of hospitalization in CICU and advanced ventilator assistance. The transmission of the virus occurs very easily from the symptomatic patient s droplets from coughing and sneezing and from direct contact with persons or surfaces. In a patient presenting with ST elevation (STEMI) myocardial infarction or STEMI-like, if positive to COVID-19, the reperfusion therapeutic strategy depends on the local organization and on the possibility to access without delay a PCI COVID Center, on the basis, obviously, of the risk/benefit assessment of the individual case. However, we advise to try pursuing, in the first instance, the mechanical revascularization strategy, according to the available local possibilities.